The Place of Political Power in the Qur'anic Worldview - mahmood fallah (رهیافتهای سیاسی و بین المللی)
One of the most important topics in the field of political science is political power. In this realm, various issues such as the principles, sources, function and goals of political power are analyzed. The answer to this question requires an explanation of the most fundamental argument, which is the origin of political power. In this study, to solve this problem, this question is examined that how examination of the concepts related to political power, can lead us to discover the origin of political power from the perspective of the Qur'an? It seems that a semantic examination of concepts related to political power such as creativity, ownership, guardianship and leadership can show the origin of political power in relation to the monotheistic worldview. The findings of this analysis, unlike the common view in the world today- which considers the source of power to be a social agreement- considers the source of political power to be a matter of divine will. In order to explain this hypothesis, an attempt is made to explain the formulation of the concept of political power from the perspective of the Qur'an and to analyze the type of relationship between the most important criteria involved in a coherent semantic network. This requires identification of key concepts related to political power and discovering its semantic field through content analysis. This study shows that there is a close relationship between politics and religion, and the concept of power in the Qur'anic way of thinking is meaningful based on the place of human in the world and the relationship between man and God. Illustrating this type of relationship gives meaning to the resources, functions, and goals of power.